Pengembangan Tanaman Multi Guna bagi Masyarakat di Kawasan Taman Hutan Raya Nipa-Nipa Kelurahan Gunung Jati, Kota Kendari - Aminuddin Mane Kandari; La Ode Agus Salim Mando Mando; Safril Kasim; La Ode Midi (Institut Pertanian Bogor, 2021)
The people of Gunung Jati Urban Village, Kendari District, Kendari City have a relatively low economic level amidst the increasing demand. The agricultural products obtained by the community are still considered unable to meet the needs of life. In addition, they are located in the area around the Nipa-Nipa Grand Forest Park (GFP) which is relatively steep and critical, so there is great concern if the community is cutting trees that could threaten forest sustainability. Therefore, the purpose of this service are 1) To provide understanding to farmers about the importance of developing multi-purpose plants and 2) Realizing forest conservation by providing multi-purpose plant seeds to be planted on community-owned land. The method of implementing the program is community-based, namely through multi-purpose plant cultivation training accompanied by assistance with counseling and discussions. The results of this service are 1) The understanding of farmers has begun to increase, namely about 18 people (72%) who already have a very good understanding of developing MPTS plants and 2) The success of planting can be seen from the percentage of seeds that grow and develop by 90% which is part of from vegetative conservation. Lack of public awareness in preserving the Tahura Nipa-Nipa including maintaining the plants that have been given, because economic pressure is still a serious obstacle. Therefore, there is still ongoing assistance with socialization and the addition of multi-purpose plant seeds in the next program.